2009
DOI: 10.1103/physreve.80.041120
|View full text |Cite
|
Sign up to set email alerts
|

Reaction under vacancy-assisted diffusion at high quencher concentration

Abstract: The theory of diffusion-mediated reactions is already established for the target problem in the dilute limit, where the immobile target is surrounded by many quenchers. For lattice random walks in the crowded situation, each quencher is surrounded by other quenchers differently. As a result, each quencher migrates differently in the presence of site blocking effects. However, in the conventional theory, such difference is ignored and quenchers are assumed to move independently of each other. In this paper, the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…However, binary scaling has shown that it is beyond the limits of binary description accuracy, and thus is insignificant at small density parameter. Such an effect is to manifest itself with increasing concentration, as is shown by numerical calculations [20,[46][47][48]. Making allowance for initial correlations in full agreement with general kinetic theory gave rise to the inhomogeneous source in the kinetic equation vanishing with time.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…However, binary scaling has shown that it is beyond the limits of binary description accuracy, and thus is insignificant at small density parameter. Such an effect is to manifest itself with increasing concentration, as is shown by numerical calculations [20,[46][47][48]. Making allowance for initial correlations in full agreement with general kinetic theory gave rise to the inhomogeneous source in the kinetic equation vanishing with time.…”
Section: Discussionmentioning
confidence: 82%
“…The influence of the interaction of the reacting pair AB with other particles (including products C) is insignificant, since taking it into consideration is beyond the limits of making allowance for two-particles only. Of course, as the density parameter increases (in this case ET is inapplicable) such a consideration becomes essential, and this is confirmed by numerical calculations available in the literature [20,[46][47][48]. However, even at small density parameters, ignoring the above force interactions in the more general GET theory that considers the dependence of pair encounters of reactants in solution determined by the contribution of three-particle correlations into the kinetics is not so apparent.…”
Section: Introductionmentioning
confidence: 82%
“…2. Earlier works [37][38][39][40][41] on the target survival for the SSEP only established some bounds on P(n = 0, T, ρ 0 ). 14), of the target survival probability for the SSEP.…”
Section: Target Survivalmentioning
confidence: 99%
“…Exceptions are provided by several particular reaction schemes in which, under some rather restrictive constraints, so-called fluctuation-induced behaviour emerges, see, e.g., [25][26][27][28][29][30][31][32][33][34] and references therein. One particular question concerns the possible concentrationdependence of the effective reaction rates [15,[35][36][37][38]. Indeed, the original Smoluchowski approach and many of its generalisations are only plausible for sufficiently low albeit finite concentrations.…”
Section: Introductionmentioning
confidence: 99%